If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39(g + -7) = 2(10 + g) Reorder the terms: 39(-7 + g) = 2(10 + g) (-7 * 39 + g * 39) = 2(10 + g) (-273 + 39g) = 2(10 + g) -273 + 39g = (10 * 2 + g * 2) -273 + 39g = (20 + 2g) Solving -273 + 39g = 20 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. -273 + 39g + -2g = 20 + 2g + -2g Combine like terms: 39g + -2g = 37g -273 + 37g = 20 + 2g + -2g Combine like terms: 2g + -2g = 0 -273 + 37g = 20 + 0 -273 + 37g = 20 Add '273' to each side of the equation. -273 + 273 + 37g = 20 + 273 Combine like terms: -273 + 273 = 0 0 + 37g = 20 + 273 37g = 20 + 273 Combine like terms: 20 + 273 = 293 37g = 293 Divide each side by '37'. g = 7.918918919 Simplifying g = 7.918918919
| -10x=-11 | | 6h+3(-h-3)=-9 | | (y-7)-(y+3)=6y | | -4(v-6)=-2+18 | | 6y-10=20+y | | 3-2x-5=16 | | 3k+15=-2(3k-6) | | -33=-6x+x+2 | | 25x-37=113 | | 7.3y-5.18= | | 2y-5x=607 | | 6x+2=8x+12-4x | | -7x+6y=-8 | | R=300+4000+.02 | | y=-2x^2-7x-5 | | 5x+1=360 | | h^2-1h=h^2-2h-12 | | 3(x+8)-2x=2(x-5)+4 | | 6n+8+4n-3= | | -28=4x-2(-2x-22) | | x+2+2x=x | | 8x-20=116-x | | -4 = z-3+ -8 | | 5x-7=3(x+y) | | 6x+8y=140 | | -5c+4(2c+7)=-43 | | 4x^2+16-32=0 | | -(-x+3)= | | [4(x+5)-8]-[3-4(x-2)]= | | 4=-8v+4(v+5) | | -5-3x-7x=-85 | | 6[1-(-3x-9)]=90x+276 |